Uzbekistan - American Cooperation in the Automobile Industry Of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2023)
This scientific article is aimed at studying the essence and consequences of U.S.-American cooperation in automotive engineering. In particular, it explores the factors that contributed to the growth of this cooperation, the problems it faced, and the potential benefits for both countries. As we study the ongoing partnership between the U.S. and the United States in automotive engineering, this research aims to highlight the importance of international cooperation in economic development, technological development and job creation in emerging markets.